Experiences and challenges in collecting survey data in an ethnically diverse social housing area. (30th September 2020) - Nygaard, S; Srivarathan, A; Mathisen, J; Kristiansen, M; Lund, R
Abstract: Socio-economically disadvantaged groups are characterised by a higher burden of disease than the background population. Paradoxically, they are often underrepresented in health research. Failing to include socio-economically disadvantaged groups in research impairs the ability to address the social mechanisms creating health disparities. The study describes how we have tried to accommodate identified challenges from the literature in conducting a questionnaire survey in a socio-economically deprived and ethnically diverse social housing area, and which new challenges we identified. The survey is planned before, during and after the structural changes take place. Through innovative approaches, we sought to accommodate identified barriers to reaching participants. The questionnaire was translated from Danish to the seven most prevalent languages in the area, based on data from the national register. A survey corps of native speaking interviewers went door-to-door to perform face-to-face interviews. To encourage participation, we used a recruitment strategy inspired by ethnographic data collection traditions, such as local presence, participation in local activities, and graphic facilitation on invitation letters. Wave 1 and 2 had a response rate of 35% (N = 209) and 22% (N = 132), respectively. 79 respondents participated in both waves. Despite our efforts to accommodate identified challenges such as language, illiteracy, and mistrust, the response rates are low. We identified new challenges in recruiting participants including participation fatigue, frustration with the restructure process, and a feeling of limited individual gain from participation. Many challenges are associated with conducting research among socio-economically disadvantaged groups. Documenting processes and learning from experiences are important steps in including groups with lower socio-economic status in health research in order to address the underlying social mechanisms creating health disparities.